Strategic Use of Role Playing in a Training Workshop for Chemistry Laboratory Teaching Assistants - Lekhi, Priyanka; Nussbaum, Sophia (Canadian Journal of Higher Education, 2015)
Many Canadian universities have created professional development programs for their teaching assistants (TA) but may be uncertain about how to bridge the gap between TAs’ knowledge of effective teaching strategies and TAs’ confident applications of these strategies. We present a technique used in a two-day training workshop to enhance graduate students skills in using effective teaching strategies: role playing. This paper outlines a framework that includes five key elements (Icebreaking, Shared Experiences, Modelling, Acting and Debriefing) to strategically design role playing activities in a training program. We describe each of the 5 elements and explain how they support training through role play exercises. Participant written feedback collected in 2010, 2011, 2012 and 2014 suggested that role playing was a useful and enjoyable technique. Pre and post workshop questionnaire data suggested that self-perceived competencies for specified tasks directly connected to a role play activity promoted greater positive differences between the pre and post groups compared to self-perceived competencies for specified tasks not directly connected to a role play activity. Based on these results, we assert that training programs which rely on strategic role playing activities will lead to a better overall TA experience of the training program and improvements in TAs’ self-perceptions of certain teaching competencies.